Chromogenic anti-Xa test: the ratio between heparin activity units and concentration of apixaban and rivaroxaban - E. V. Titaeva; A. B. Dobrovolsky (Атеротромбоз)
Introduction. The direct oral anticoagulants (DOC) therapy does not require alaboratory control; however, it may be required to determine the anticoagulationlevel to choose a treatment strategy if alarge bleeding is developing or emergency surgery is needed.The objective of this experimental study was to investigate the relationship between the residual factor Xa (FXa) activity, anti-Xa activity units oflow molecular weight heparins (LMWH), and the apixaban and rivaroxaban plasma concentrations in a chromogenic anti-Xa assay.Material and methods. Concentrated DOC solutions were prepared by extracting apixaban and rivaroxaban from crushed tablets using methanol and dimethyl sulfoxide, respectively. The resulting solutions were added to the donor plasma pool until final inhibitor concentrations are achieved in the range from 10 to 100 ng/ml plasma. Anti-Xa activity was determined using an STA-compact analyser and the Liquid anti-Xa reagent kit, an analysis protocol, and calibrators designed to control the LMWH therapy. The effect on the thrombin formation dynamics was investigated using the thrombin generation test (TGT) and the PPR reagent as a trigger (final concentrations of tissue factor are 5 pM, and those of phospholipids are 4 μM). TGT curves were analysed using the Thrombinoscope program.Results. It was shown that in the anti-Xa activity test version designed to control the LMWH therapy, there is a high correlation (R2 > 0.98) between thelogarithm of the residual factor Xa activity and the content of apixaban and rivaroxaban in the range from 10 to 80 ng/ml. Rivaroxaban shows about 1.5 times more anti-Xa activity than apixaban at equal concentrations. It was also shown that apixaban and rivaroxaban at doses equal both in concentration and in anti-Xa activity differ in their effect on the thrombin formation dynamics and thrombin inactivation in the TGT.Conclusion. In the LMWH anti-Xa activity test version, the measured range of apixaban and rivaroxaban includes 30 ng/ml and 50 ng/ ml concentrations taken as “cut-off points” to determine the treatment tactics in emergency cases. However, thelack of certified DOC calibratorslimits the use of this test in clinical practice.